Data-driven three-dimensional reconstruction of human bodies using a mobile phone app. (2016) - Ballester, Alfredo; Parrilla, Eduardo; Piérola, Ana; Uriel, Jordi; Pérez, Cristina; Piqueras, Paola; Nácher, Beatriz; Vivas, Julio A.; Alemany, Sandra
The advances and availability of technologies for the acquisition, registration and analysis of the three-dimensional (3D) shape of human bodies (or body parts) are resulting in the formation of large databases of parameterised meshes from which digital human body models can be derived. Such models can be used for the data-driven reconstruction of parameterised human body shapes from partial information such as one-dimensional (1D) measurements or 2D images. In this paper, we propose a new method for the reconstruction of 3D bodies from images gathered with a smartphone or tablet. Moreover, the method is implemented into a prototype app and tested at different levels through three experimental studies including synthetic models, 1:10 scale figurines and real children. The results demonstrate the feasibility of acquiring reliable anthropometric information easily at home by non-experts. This method and implementation have great potential for their application to the personalisation, size recommendation and virtual try-on simulation of wearable products.